Pengaruh Penyelenggaraan Otonomi Desa Terhadap Peningkatan Pembangunan Di Desa Komering Agung Kecamatan Gunung Sugih Kabupaten Lampung Tengah - Agustuti Handayani (PUBLICA, 2011)
Village is the unity of law society that has area borders and it also an authority to regulate and to take care the local society interest according to the local admitted and respected origin and culture in the Government System of Republic of Indonesia. In the effort of running the village government, therefore, the village development plan is arranged as a unity included in the regency or city development plan. The village development plan is set by the participative of village government according to its authority. The formulation of the problem in this research is : Does the autonomy village program have the significant influence toward the development improvement in Komering Agung village, Gunung Sugih sub-district, Central Lampung regency?. Therefore the objective of this research is to know how big is the influence of the autonomy village program toward the development improvement in Komering Agung village, Gunung Sugih sub-district, Central Lampung regency. In this research, the data sources are taken from secondary and primary data using the qualitative and quantitative data analysis. As the result of this research, it can be concluded that the autonomy village program in Komering Agung village, Gunung Sugih, Central Lampung has been conducted well. It can identified from the result of questionnaire given to 34 respondents of this research and it showed that 19 or (55,88%) respondents stated that the autonomy village program run in Komering Agung village, Gunung Sugih sub-district, Central Lampung regency has been done well. However, it is suggested that there must be a good cooperation and awareness between the government apparatus and society in running the autonomy village program in order to support the development improvement in Komering Agung village Gunung Sugih sub-district, Central Lampung regency